Characterization and toxicology evaluation of chitosan nanoparticles on the embryonic development of zebrafish, Danio rerio. (5th May 2016) - Wang, Yanbo; Zhou, Jinru; Liu, Lin; Huang, Changjiang; Zhou, Deqing; Fu, Linglin
Graphical abstract: Highlights: Chitosan nanoparticles were prepared and characterized. Zebrafish was used to evaluate the embryonic toxicology of chitosan nanoparticles. Mortality rate was lower in the groups treated with chitosan nanoparticles. Groups treated with normal chitosan particles showed more embryos malformation. Chitosan nanoparticles were more secure compared with normal chitosan particles. Abstract: In the present study, chitosan nanoparticles were prepared, characterized and used to evaluate the embryonic toxicology on zebrafish ( Danio rerio ). The average particle size of chitosan nanoparticles was 84.86 nm. The increased mortality and decreased hatching rate was found in the zebrafish embryo exposure to normal chitosan particles and chitosan nanoparticles with the increased addition concentration. At 120 h post-fertilization (hpf), the rate of mortality were 25.0 and 44.4% in the groups treated with chitosan nanoparticles and normal chitosan particles at 250 mg/L, respectively. At 72 hpf, the hatching rate in the groups treated with normal chitosan particles were lower ( P < 0.01) at 300 and 400 mg/L than those of the corresponding control groups, respectively. However, there were no significant differences between the groups treated with chitosan nanoparticles and the control groups across all the addition concentrations. More abundant typical malformation of embryos was observed in the groups treated with normal chitosan particles compared with those treated with chitosan nanoparticles. The LC50 (medium lethal concentration) of chitosan nanoparticles was 280 mg/L at 96 hpf and 270 mg/L at 120 hpf. As for normal chitosan particles, the LC50 was 257 mg/L at both 96 hpf and 120 hpf. The TC50 (medium teratogenic concentration) of the zebrafish treated with chitosan nanoparticles and normal chitosan particles were 257 mg/L and 137 mg/L, respectively. It indicated that the chitosan nanoparticles were relatively more secure compared with normal chitosan particles.